Comparison between endoscopic ultrasound-guided fine-needle biopsy and bite-on-bite jumbo biopsy for sampling of subepithelial lesions. Issue 5 (May 2022) - Facciorusso, Antonio; Crinò, Stefano Francesco; Ramai, Daryl; Ofosu, Andrew; Muscatiello, Nicola; Mangiavillano, Benedetto; Lamonaca, Laura; Lisotti, Andrea; Fusaroli, Pietro; Gkolfakis, Paraskevas; Stasi, Elisa; Samanta, Jayanta; et al.
Abstract: Background and Aims: A direct comparison between endoscopic ultrasound (EUS) fine-needle biopsy (FNB) and current endoscopic biopsy techniques in patients with subepithelial lesions (SELs) is still lacking. Aim of this multicenter study was to compare the diagnostic performance and safety profile between EUS-FNB and bite-on-bite jumbo biopsy. Methods: Out of 416 patients undergoing endoscopic sampling of SELs between 2017 and 2021, after propensity score matching two groups were compared: 120 undergoing EUS-FNB and 120 sampled with bite-on-bite jumbo biopsy. Primary outcome was sample adequacy. Secondary outcomes were diagnostic accuracy, sensitivity, specificity, and adverse events. Results: Median age was 61 years and most patients were male in both groups. Final diagnosis was GIST in 65 patients (54.1%) in the EUS-FNB group and 62 patients in the bite-on-bite biopsy group (51.6%; p = 0.37). Sample adequacy was significantly higher in the EUS-FNB group as compared to the bite-on-bite biopsy group (94.1% versus 77.5%, p <0.001). EUS-FNB outperformed bite-on-bite biopsy also in terms of diagnostic accuracy (89.3% versus 67.1%, p <0.001) and sensitivity (89% vs 64.5%; p <0.001), whereas specificity was 100% in both groups ( p = 0.89). These findings were confirmed in subgroup analysis according to SEL location, final diagnosis, and wall layers of the sampled SEL. Adverse event rate was 6.6% in the EUS-FNB group and 30% in the bite-on-bite biopsy group ( p <0.001). Conclusion: EUS-FNB outperforms bite-on-bite biopsy both in terms of diagnostic yield and safety profile.